Trimodal glioblastoma treatment consisting of concurrent radiotherapy, temozolomide, and the novel TGF-β receptor I kinase inhibitor LY2109761 - Zhang, Mengxian; Herion, Tobias W.; Timke, Carmen; Han, Na; Hauser, Kai; Weber, Klaus-Josef; Peschke, Peter; Wirkner, Ute; Lahn, Michael; Huber, Peter E. (Neoplasia, 2011)
Here we investigate the effects of the novel transforming growth factor-β receptor I (TGF-βRI) serine/threonine kinase inhibitor LY2109761 on glioblastoma when combined with the present clinical standard combination regimen radiotherapy and temozolomide (TMZ). Human GBM U87 (methylated MGMT promoter), T98 (unmethylated MGMT promoter), and endothelial cells (HUVECs) were treated with combinations of LY2109761, TMZ, and radiation. We found that LY2109761 reduced clonogenic survival of U87 and T98 cells and further enhanced the radiation-induced anticlonogenicity. In addition, LY2109761 had antimigratory and antiangiogenic effects in Matrigel migration and tube formation assays. In vivo, in human xenograft tumors growing subcutaneously on BALB/c nu/nu mice, LY2109761 delayed tumor growth alone and in combination with fractionated radiation and TMZ. Interestingly, as expected, the methylated U87 model was more sensitive to TMZ than the unmethylated T98 model in all experiments, whereas the opposite was found for LY2109761. Moreover, with respect to tumor angiogenesis, while LY2109761 decreased the glioblastoma proliferation index (Ki-67) and the microvessel density (CD31 count), the relative pericyte coverage (α-SMA/CD31 ratio) increased in particular after triple therapy, suggesting a vascular normalization effect induced by LY2109761. This normalization could be attributed in part to a decrease in the Ang-2/Ang-1 messenger RNA ratio. LY2109761 also reduced tumor blood perfusion as quantified by noninvasive dynamic contrast-enhanced magnetic resonance imaging. Together, the data indicate that the addition of a TGF-βRI kinase inhibitor to the present clinical standard (radiation plus TMZ) has the potential to improve clinical outcome in human glioblastoma, especially in patients with unmethylated MGMT promoter status.
Available online 4 March 2014
Gesehen am 16.01.2023